The Development of Lectora Inspire-Based Interactive Learning on General Administration Subject - Akbarini, Nur Rahmi; Murtini, Wiedy; Rahmanto, Andre N (Dinamika Pendidikan, 2018)
This study was a research and development type. The media developed was a lectora inspire-based interactive learning media in general administration subject. The procedure of research and development employed nine out of ten steps of Borg Gall’s research and development (1989). Data analysis was carried out using descriptive qualitative and quantitative analyses with t-test. Considering the result of analysis on the effectiveness of lectora inspire-based interactive learning media with t-test formula, it could be found that t-statistic value obtained in posttest of experiment and control class was 5.747, with ttable of 2.000172; thus tstatitic ttable meaning that the improvement of learning outcome in experiment class was better than that in control class. The learning outcome of experiment class showed the mean post-test of 84.53, while that of control class showed the mean posttest of 71.73. The conclusion of research was that Lectora Inspire-based interactive learning media was feasible and was used effectively to improve the students’ learning outcome. It was based on the result of t-test suggesting the significance value (0.0000.05), indicating that there is a difference of learning outcome between experiment class and control class